Produção de grãos, matéria seca e acúmulo de nutrientes em culturas submetidas à adubação orgânica e mineral - Ciancio, Nathalia Haydee Riveros (2010)
In Brazil, one of the main activities on small farms is the creation of small animals. The waste produced in this activity can be used as an alternative fertilizer because it contains a number of chemicals readily available or after the process of mineralization can be absorbed by plants. However, the imbalanced composition of the organic fertilizers because of the type of feed and age of animals, in addition to the waste managed data hinders the recommendation and standardization of doses to be applied. Aiming to evaluate different increasing doses of organic fertilizers supplemented with mineral fertilizer topdressing evaluated the yield, production of dry matter accumulation of nutrients (N, P, K, Ca and Mg) in crops of beans, corn, sorghum and oats. The study was conducted in two experimental areas. In the period 2005 to 2008 we used the experimental area of Department of Soil UFSM / RS. In the period 2008 to 2009 was performed on a rural property located in the district of Boca del Monte, Santa Maria (RS). The soils of these two areas were classified as sandy clay loam Ultisol second Embrapa (2006). The treatments at doses of 10, 20 and 30 m3ha-1 of pig slurry and 1 and 2 t ha-1 manure turkey without and with supplementation of mineral N in coverage. Apart from these treatments, we evaluated the recommendation minerals (NPK) according to CQFS-RS/SC (2004). The data on grain yield of beans and corn, dry matter (DM) and nutrient accumulation were subjected to statistical analysis by contrast. The results showed that doses of 30 m3ha-1 of pig slurry and 2 t ha-1 manure turkey complemented with mineral N in coverage favored the grain yield, dry matter production and accumulation of nutrients. The rate of utilization of N, P and K by plants boosted by intermediate doses of 10 m3ha-1 with and without mineral N in coverage, noting that doses above 30 m3ha-1 of pig slurry, in addition to being less efficient to plant nutrition, potentiate the risk of contamination of soil and water.